Ecosystem services of 'Trees Outside Forests (TOF)' and their contribution to the contemporary sustainability agenda: a systematic review. (1st November 2022) - Peros, Colin Scott; Dasgupta, Rajarshi; Estoque, Ronald C; Basu, Mrittika
Abstract: Trees Outside Forests (TOF) were recognized in the United Nations Food and Agricultural Organization's 2000 Global Forest Resource Assessment as an essential component of sustainable development. Today, however, TOF remain an undervalued resource, with no comprehensive review of the wide spectrum of ecosystem services that are provided by TOF nor of the diversity of tree species that comprises TOF globally. Thus, a global analysis of TOF is vital to quantify their contribution to sustainable development and international climate initiatives. We reviewed the scientific literature to (1) classify and compile a repository of information on TOF resources, including the types of ecosystem services provided by TOF, geographic distribution, land-use type, and spatial pattern; and (2) document the diversity of tree species that comprises TOF globally. After screening the literature, 203 species of TOF were investigated across 20 countries in the 28 articles that we analyzed; another 15 articles across 57 countries did not include taxonomic information. Our results showed that the global distribution of TOF studies was biased toward Europe, revealing data deficiencies across the Global South, despite its contribution to biodiversity and ecosystem services. We also observed a bias in ecosystem service type toward regulating and supporting services, with studies lacking in cultural and provisioning services provided by TOF. Furthermore, studies conducted in urban areas were also lacking. To realize the full potential of TOF for sustainable development and climate initiatives, we conclude that a more holistic understanding of their ecosystem services must be established under national and intergovernmental reporting mechanisms.